Assuming the Challenge of Developing Research Projects in Occupational Health Nursing - González-Caballero, Javier (La Medicina del Lavoro, 2023)
In today's society of uncertainty, we are witnessing a transformation of the economic, social, demographic, digital, ecological, and employment model, which faces unforeseen challenges. These challenges require reflecting beyond their consequences, and new workplace risks call for a debate on solutions beyond traditional ones. In the specific context of companies, the main functions of occupational health nursing are to prevent, promote, protect, and restore workers’ health. The integration of research into nursing practice entails the better implementation of scientific advances. Although in the real world of professional nursing practice, there is a discrepancy between the knowledge obtained through research and clinical practice, practicing based on care plans, solid practice guidelines, and scientific evidence is a maxim.